Performance of smart beta ETFs in the U.S. market: 2009–2019 - CHIRAPHOL, Chiyachantana N. (Institutional Knowledge at Singapore Management University, 2022)
Purpose: This paper empirically analyses the performance of smart beta exchange traded funds (ETFs) through the absolute return, relative return, and risk-adjusted return over the decade from 2009 to 2019.Methodology: Using a sample of smart beta ETFs in the U.S. stock market, we examine the components of the risk factors in a smart beta strategy. Results: Our results show that a smart beta strategy is not able to maintain a persistent performance over the period examined. Moreover, there is not a single year that smart beta ETFs could generate an abnormal return that is statistically significant. The evidence illustrates that returns of smart beta ETFs do not significantly beat the S&P 500 market benchmark on an absolute, relative, and risk-adjusted return basis.